Socio-Economic Pathways to Rice Farming Productivity: Evidence from Institutional and Input-Based Mediation in Kupang Regency - Micha S. Ratu Rihi; Viona Nainggolan; Ramses Victor Elim; Saidin Nainggolan (Randwick International of Social Science Journal, 2026)
Rice farming productivity in Kupang Regency remains relatively low and is influenced by social, economic, and institutional factors. This study aims to analyze the effects of farmers’ social and economic characteristics on institutional access, production input use, and rice farming performance using a Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The research was conducted in Central Kupang District with a sample of 75 rice farmers selected through simple random sampling from three purposively chosen villages. Primary data were collected through structured interviews and analyzed using SmartPLS. The results show that social factors significantly affect production input use and farm performance but do not significantly influence institutional access. Economic factors have a significant effect on production input use and farm performance, while their direct effect on institutional access is not significant. Institutional access significantly affects production input use but has a negative direct effect on farm performance. Production input use is confirmed as the main mediating variable transmitting the effects of social, economic, and institutional factors on farm performance. The structural model demonstrates strong explanatory power with an R² value of 0.856. These findings indicate that improving rice productivity cannot rely solely on strengthening institutional access, but must be accompanied by the effective and efficient use of production inputs. Policy implications emphasize the importance of enhancing farmers’ economic capacity and optimizing input utilization as key strategies to improve rice farming productivity in Kupang Regency.